Sexual Activity before Sports Competition: A Systematic Review - Stefani, Laura; Galanti, Giorgio; Padulo, Johnny; Bragazzi, Nicola L.; Maffulli, Nicola (Frontiers in Physiology, 2016)
Sexual activity before competition has been considered as a possible cause for reduced performance since ancient Greece and Rome. Recently, the hypothesis that optimal sport performance could be influenced by a variety of factors including sexual activity before competition has been investigated. However, few scientific data are available, with the exception of anecdotal reports of individual experiences. The present systematic review focused on the current scientific evidence on the effects of sexual activity on sport performance regardless of sport type. Data were obtained following the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) guidelines, using PubMed/MEDLINE, ISI/Web of Science, the Cochrane Collaboration Database, Cochrane Library, Evidence Database (PEDro), Evidence Based Medicine (EBM) Search review, National Guidelines, ProQuest, and Scopus, all searched from inception Further, to broaden the search, no time filter nor language restriction have been applied. Also, the gray literature was mined using Google Scholar. Only relevant scientific articles reporting outcomes of athletic performance after sexual activity were considered. The impact of sexual activity before a sport competition is still unclear, but most studies generally seem to exclude a direct impact of sexual activity on athletic aerobic and strength performance. The most important aspect seems to be the interval from the time of the sports competition that affects negatively the performance if it is shorter than two hours. There are possible negative effects from some possible concurrent wrong behaviors such as smoking or alcohol abuse. There are no investigations about the effect of masturbation in this context. There is a need to clarify the effects of sexual activity on competition performance. The present evidence suggests that sexual activity the day before competition does not exert any negative impact on performance, even though high-quality, randomized controlled studies are urgently needed.